Overexpression of FAM46A, a Non-canonical Poly(A) Polymerase, Promotes Hemin-Induced Hemoglobinization in K562 Cells - Lin, Hsi-Hsien; Lo, Yu-Ling; Wang, Wen-Chih; Huang, Kuan-Yeh; I, Kuan-Yu; Chang, Gin-Wen (Frontiers in Cell and Developmental Biology, 2020)
FAM46A belongs to the FAM46 subfamily of the nucleotidyltransferase-fold superfamily and is predicted to be a non-canonical poly(A) polymerase. FAM46A has been linked to several human disorders including retinitis pigmentosa, bone abnormality, cancer, and obesity. However, its molecular and functional characteristics are largely unknown. We herein report that FAM46A is expressed in cells of the hematopoietic system and plays a role in hemin-induced hemoglobinization. FAM46A is a nucleocytoplasmic shuttle protein modified by Tyr-phosphorylation only in the cytosol, where it is closely associated with ER. On the other hand, it is located proximal to the chromatin regions of active transcription in the nucleus. FAM46A is a cell cycle-dependent poly-ubiquitinated short-lived protein degraded mostly by proteasome and its overexpression inhibits cell growth and promotes hemin-induced hemoglobinization in K562 cell. Site-directed mutagenesis experiments confirm the non-canonical poly(A) polymerase activity of FAM46A is essential for enhanced hemin-induced hemoglobinization. In summary, FAM46A is a novel poly(A) polymerase that functions as a critical intracellular modulator of hemoglobinization.